Do orthopedic corrections of growing retrognathic hyperdivergent patients produce stable results? - Rice, Alec J. (Angle Orthod, 2019)
OBJECTIVES: To determine if posterior dental intrusion produces stable orthodontic and orthopedic corrections in growing retrognathic hyperdivergent patients. MATERIALS AND METHODS: The sample included 14 subjects (five males and nine females), who were 13.4 ± 0.7 years pretreatment, treated for 3.5 years, and followed for 3.6 years posttreatment. During the initial orthopedic phase, 150 g NiTi coil springs were attached to two palatal miniscrew implants (MSIs) for maxillary intrusion; two buccal mandibular MSIs were used for posterior vertical control. Full orthodontic therapy was initiated to correct the malocclusions during the orthodontic phase. Patients were recalled a minimum of 1 year posttreatment (mean 3.6 ±1.6 years). Patients were compared to matched untreated controls. RESULTS: Relative to the untreated controls, during treatment and retention, maxillary and mandibular molars underwent 2.8 mm and 3.7 mm of relative posterior intrusion, respectively. Maxillary incisors were extruded 1.3 mm and the mandibular incisors underwent 2.9 mm of relative intrusion. Overall orthopedic changes included a reduction in the mandibular plane angle (MPA; 3.3°), an increase in SN-Pg (2.4°), an increase in S-N-B (2.1°), and a 4.3 mm relative reduction in anterior facial height. The maxillary incisors, which showed 0.6 mm of intrusion (relative to controls), was the only dental or skeletal measure to show a statistically significant between-group posttreatment difference. CONCLUSIONS: Except for maxillary incisor position, the substantial dental intrusion and associated orthopedic corrections that were produced during treatment remained stable post-treatment.